Fear of progression, loneliness, and hope in patients with gastrointestinal cancer: a cross-sectional relational study - Li, Yanjun; Xiao, Tian; Liao, Haiyan; Qu, Haimei; Ren, Pan; Chen, Xiaoju (Frontiers in Psychology, 2024)
Introduction In recent years, fear of disease progression (FoP) has become one of the most common psychological problems in cancer patients. However, there are fewer studies on the FoP in patients with gastrointestinal tumors. We aimed to assess the level of FoP in patients with gastrointestinal tumors and analyze the factors related to FoP. We also aimed to examine the relationship among loneliness, hope and FoP in patients with gastrointestinal cancer. Methods A cross-sectional survey was conducted on three Grade A hospitals in southwestern China from November 2021 to July 2022. The demographic and clinical characteristics questionnaire, Fear of Disease Progression Scale (FoP-Q-SF), Cancer Loneliness Scale (CLS), and Herth Hope Index (HHI) were included in this study. Data analysis included descriptive statistics, independent samples t-tests, one-way analysis of variance, and multiple linear regression analysis. Results In total, 245 gastrointestinal cancer patients participated in this study. The average (standard deviation) FoP score in patients was 32.94 ± 10.64. In total, 245 gastrointestinal cancer patients participated in this study. The average (standard deviation) FoP score in patients was 32.94 ± 10.64. The average score of CLS was 17.65 ± 6.71, and that for the HHI was 31.27 ± 7.73. Pearson correlation analysis showed that FoP was negatively significant correlated with hope level (r = −0.522) and FoP was positively significant correlated with loneliness (r = 0.545). Linear regression analysis showed that educational level, age, living condition, hope, and loneliness were the significant predictors of FoP and explained 53.10% of the variability in FoP (F = 16.372). Conclusion Findings highlight the need to strengthen attention to FoP in gastrointestinal cancer patients. Our study showed that gastrointestinal cancer patients who have a high school education, are age 45 to 59, live alone, high level of loneliness, and low level of hope have higher FoP. Medical staff should enhance clinical screening of FoP and consider the formulation of relevant interventions for high-risk groups to reduce loneliness among patients, raise their hope level, and reduce their FoP.